An Analysis of Students' Errors in Constructing the Concept of Integer Operations Based on Assimilation and Accommodation - Kurniati, Dian; A’yun, Qurrota; Jatmiko, Dhanar Dwi Hary; Pambudi, Didik Sugeng; Oktavianingtyas, Ervin; Sutarto, Sutarto; Osman, Sharifah (Universitas Islam Negeri Raden Intan Lampung, 2025)
Errors in constructing concepts often occur in mathematics learning, especially in the topic of integer operations. These errors arise because students tend to memorize procedures or rules without fully understanding the underlying concepts. This research aims to analyze students' errors in constructing the concept of integer operations based on assimilation and accommodation. This study uses a qualitative method with 16 students from class VII B at MTs Baitul Hikmah Tempurejo as subjects. The data collection methods in this study included tests and interviews. Data analysis was carried out through the stages of analyzing test results, conducting interviews, and triangulating the data to ensure validity. Based on the analysis and discussion of the data, it can be concluded that all subjects experienced errors in constructing the concept. Four types of concept construction errors were identified: Pseudo Construction, Construction Hole, Mis-logical Construction, and Mis-analogical Construction. Pseudo Construction occurs when a student merely memorizes phrases like